Study of the occurrence of airborne Polycyclic Aromatic Hydrocarbons associated with respirable particles in two coastal cities at Eastern Mediterranean: Levels, source apportionment, and potential risk for human health. (15th September 2019) - Iakovides, Minas; Stephanou, Euripides G.; Apostolaki, Maria; Hadjicharalambous, Marios; Evans, John S.; Koutrakis, Petros; Achilleos, Souzana
Abstract: Polycyclic Aromatic Hydrocarbons (PAHs) are one of the most hazardous substances in the environment. Although their occurrence and fate in the atmosphere of Eastern Mediterranean is well documented, there is limited information on PAH levels in the inhalable aerosol fraction. Additionally, to the best of our knowledge, there is lack of information on particulate matter with aerodynamic diameter equal or less than 2.5 and 10 μm (PM2.5 /PM10 )-bound PAH concentrations and sources in Cyprus. We therefore present the first study that i) determines the concentration levels of PAHs in the respirable and inhalable (PM2.5 and PM10 ) fraction of particulate matter; ii) identifies, quantifies, and compares PAH emission sources by applying two receptor models (Principal Components Analysis/Multiple Linear Regression Analysis, PCA/MLR; and UNMIX factorization), and iii) assesses their relative toxicity at two different coastal sites in Eastern Mediterranean (Island of Crete, Greece; and Cyprus). For this purpose, a total of 79 samples were collected in Heraklion (Island of Crete) and Limassol (Cyprus) during a 2-year sampling campaign between 2012 and 2014. Thirty five PAH members were identified and the total concentration (Σ35 PAHs) levels in PM2.5 ranged between 0.15 and 9.19 ng/m 3 in Heraklion; 0.12 and 3.91 ng/m 3 (PM2.5 ), and 0.16 and 4.02 ng/m 3 (PM10 ) in Limassol. PAH concentrations were the highest when air masses were passing over highly polluted areas, such as the eastern Balkan Peninsula/Adriatic Sea and northern Greece. The most abundant members at both sites were Benzo[b]fluoranthene (7–16%), Benzo[e]pyrene (8–11%), Indeno[1, 2, 3-cd]pyrene (10–18%) and Benzo[ghi]perylene (9–21%); as well as Anthranene (5–6%) and Coronene (9–11%) in Limassol. The major PAH emission sources obtained from the application of PCA/MLRA were gasoline and diesel/coal combustion sources, accounting for almost 60% and 40% of total contribution in Heraklion, while in Limassol both sources contributed nearly equally (51% and 49%, respectively). Similar findings were obtained using the UNMIX model. The lifetime incremental cancer risk (ILCR) due to both inhalation and ingestion exposure from particulate PAHs was well below the U.S. EPA regulatory threshold in both study areas. Highlights: The most abundant PAH members in Crete-Greece and Cyprus were BbF, BeP, IP, and BghiP. Gasoline and diesel/coal combustion were the main sources of PAHs at both sites. PAH levels reached max when air masses were passing over highly polluted countries. The most important contributors to cancer burden were BaP (∼50%), BbF, DBA, and IP.